Metabolite correlation with antioxidant activity in different fruit maturation stages of Physalis peruviana (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mubarok S, Wicaksono FY, Budiarto R, Rahmat BPN, Khoerunnisa SA. 2021. Metabolite correlation with antioxidant activity in different fruit maturation stages of Physalis peruviana. Biodiversitas 22: 2743-2749. Fruit development influences the metabolites contents and then its biological activity, however, such report is still limited in goldenberry (Physalis peruviana L.). This work aimed to evaluate metabolite variability and its correlation to antioxidant activity in several stages of fruit maturation in goldenberry originating from Sumedang, Indonesia. The research was laid out in a completely randomized design with 6 different treatments in terms of fruit maturation stages. Only fresh and pest-disease-free fruits collected from local farms were prepared for several metabolites assay, i.e pH, TSS, lycopene, ?-carotene, polyphenol, flavonoid and its antioxidant activity. The statistical analysis resulted in a significant improvement of all fruit metabolite variables in response to fruit maturation process, except polyphenol. Compared to the oldest fruit stage of S6 (orange berry covered by full wilt white calyx), the youngest fruit of S1 (green berry covered by fresh green calyx) increased the pH, TSS, lycopene, ?-carotene and flavonoid by about 7%, 67.5%, eight-fold, nine-fold and two-fold, respectively. Pearson correlation analysis showed a significant and positive correlation between all metabolite variables (except polyphenol) to antioxidant activity of goldenberry fruit.
Keywords: lycopene; flavonoid; polyphenol; β-carotene; goldenberry; TSS